PEMETAAN TREN, MODEL, DAN KESENJANGAN PENELITIAN PEMBELAJARAN BAHASA INDONESIA MI/SD DALAM MENDUKUNG LITERASI ABAD 21: SYSTEMATIC LITERATURE REVIEW - Nursalim; Rahmat Umara, Alifiyoni; Aulia, Aziqri; Khoirani, Suci (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to map trends, models, and gaps in Indonesian language learning research in MI/SD in supporting 21st century literacy through a Systematic Literature Review (SLR) approach. The search process was conducted systematically in reputable scientific databases using keywords related to “Indonesian language learning,” “MI/SD,” and “21st century literacy.” Based on the established inclusion and exclusion criteria, 20 articles were obtained and analyzed in depth. The synthesis results show that research trends are dominated by the development of literacy-based learning models, digital technology integration, and Higher Order Thinking Skills (HOTS)-based approaches. The models that are widely used include Problem Based Learning, Project Based Learning, and text-based learning. However, a research gap was found in the aspects of longitudinal evaluation, comprehensive integration of digital literacy, and the development of contextual 21st-century literacy assessment instruments for MI/SD levels. This study contributes a conceptual map and recommendations for further research directions to strengthen Indonesian language learning that is adaptive to the demands of 21st-century competencies.